Coexistence of Solitary Fibrous Tumor in the Small Bowel Wall with Mesentery Neuroendocrine Tumor: A First Case Report - Salazar CG; Serei VD; Grandhi MS; Zhou Z (Dove Medical Press, 2021)
Cristo G Salazar,1 Virian D Serei,1 Miral S Grandhi,2 Zhongren Zhou1 1Department of Pathology & Laboratory Medicine, Robert Wood Johnson Medical School, Rutgers University, New Brunswick, NJ, 08903, USA; 2Division of Surgical Oncology, Rutgers Cancer Institute of New Jersey and Rutgers Robert Wood Johnson Medical School, New Brunswick, NJ, 08901, USACorrespondence: Zhongren ZhouChief of Gastrointestinal Pathology, Department of Pathology & Laboratory Medicine, Robert Wood Johnson Medical School, 125 Paterson Street,(MEB 233), New Brunswick, NJ, 08903, USATel +1 732-667-0497Fax +1 732-235-8124Email zz442@rwjms.rutgers.eduBackground: Solitary fibrous tumor (SFT) of the small bowel wall is a rare occurrence with only one case reported to date. SFT in the small bowel wall adjacent to mesenteric neuroendocrine tumor has not been reported, to the best of our knowledge, in the English literature.Case Presentation: The patient is an 82-year old male with a right perinephric mass incidentally diagnosed during a bladder ultrasound for working-up of chronic urinary tract infections. A follow-up CT of the abdomen and pelvis demonstrated a mass located to the right of the pancreatic head and anterior to the duodenum. A subsequent endoscopic ultrasound (EUS) with fine needle biopsy of the mass diagnosed a low-grade neuroendocrine tumor, which was supported by positivity for CD56, synaptophysin, and chromogranin. An exploratory laparotomy was performed, and the mesenteric mass was identified near the root of the middle colic vessels and laying on top of the duodenum and pancreatic head. A right hemicolectomy with terminal ileum resection was performed en bloc with resection of the mesenteric mass, presumed to be a large lymph node metastasis. A small white-tan, firm nodule was located within the small bowel submucosa and identified, measuring 0.6 x 0.4 x 0.3 cm. The mesenteric mass measured 5.5 x 3.5 x 3.3 cm and was in the mesenteric drainage distribution of the small bowel. The mesentery tumor cells were positive for synaptophysin and chromogranin, which supported the diagnosis of neuroendocrine tumor. The small submucosal nodule cells were positive for STAT6, CD34 and CD99, and focally positive for BCL-2, which confirmed the diagnosis of SFT of the small bowel.Conclusion: We report the first case of SFT within the small bowel submucosa coexisting with a large neuroendocrine tumor within the mesentery.Keywords: solitary fibrous tumor, neuroendocrine tumor, small bowel, coexistence